Perceived value of organizational foresight processes: effects of the illusion of control and individual foresight - Borges, Natália (2021)
This research proposes an investigation into the reasons for low adherence for foresight processes in organizations. Studies involving the relevance of foresight processes have become increasingly frequent, driven by an environment of increasing volatility, uncertainty, ambiguity, and complexity. Despite the importance of the topic, which seeks to enable organizations to anticipate threats and opportunities from the environment through methods, thereis still little adherence to these practices, which justifies the purpose of this investigation. To achieve the proposed objective, a questionnaire was structured. Then, it was applied via electronic survey, allowing the observation of the effects of the illusion of control and individual foresight activities on the perceived value of formal foresight processes in organizations. The data were analyzed based on structural equations modeling with estimation through Partial Least Square (PLS). The sample was composed of 185 executives from the financial and technological sectors, and a reduction to the perceived value of foresight processes was identified, as a result of the illusion of control and individual practices of these activities. These results contribute to the understanding of the low adherence of foresight processes, from the perspective of cognitive biases attributed to the decision-maker.